A fast and powerful swimming microrobot with a serrated tail enhanced propulsion interface. Issue 42 (13th September 2018) - Li, Dengfeng; Liu, Yanting; Yang, Yuanyuan; Shen, Yajing
Abstract : A serrated tail with multiple channels and nanointerfaces is used for the first time in a 3D swimming microrobot to enhance chemical reaction interfaces and realize powerful high-speed motion. Abstract : We demonstrate the use of a swimming microrobot with a serrated tail in the propulsion region to enhance reaction interfaces. A 3D printed tail with multiple catalytic channels and nanointerfaces could reinforce the microrobot, allowing it to reach swimming speeds of ∼1 mm s −1 and enabling it to transport objects with a weight 6500 times that of itself. This research represents a new concept in swimming microrobot design and is expected to benefit a wide range of engineering fields.